1992
DOI: 10.1002/jsfa.2740600102
|View full text |Cite
|
Sign up to set email alerts
|

Glucosinolate responses of swede, kale, forage and oilseed rape to root damage by turnip root fly (Delia floralis) larvae

Abstract: Two genotypes of kale (Brassica olerucea L). two of rape (one forage and one winter oilseed type, B riapus L) and two of swede ( B rtupus L) grown in a glasshouse were inoculated with turnip root fly (Deliafloralis Fall) eggs at 5 weeks and their roots, stems and leaves sampled after a further 8 weeks of larval feeding. Changes in total and individual glucosinolates were examined in roots, stems and leaves after attack. Damage by Dflorulis larvae to roots caused tissue weight losses in roots ranging from 26 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 26 publications
1
56
0
Order By: Relevance
“…Induction of secondary metabolites in roots due to root feeding by insect larvae has been reported for a number of plant and herbivore combinations (Birch et al 1992;Bezemer et al 2003Bezemer et al , 2004Borowicz et al 2003;Van Dam and Raaijmakers 2006) and might be a general plant response similar to aboveground induction due to shoot herbivores (Karban and Baldwin 1997). Irrespective of plant line, wireworms had no significant effect on root biomass, but led to an increase in leaf biomass, pointing to compensatory shoot growth (Wurst and Van der Putten 2007).…”
Section: Discussionmentioning
confidence: 80%
“…Induction of secondary metabolites in roots due to root feeding by insect larvae has been reported for a number of plant and herbivore combinations (Birch et al 1992;Bezemer et al 2003Bezemer et al , 2004Borowicz et al 2003;Van Dam and Raaijmakers 2006) and might be a general plant response similar to aboveground induction due to shoot herbivores (Karban and Baldwin 1997). Irrespective of plant line, wireworms had no significant effect on root biomass, but led to an increase in leaf biomass, pointing to compensatory shoot growth (Wurst and Van der Putten 2007).…”
Section: Discussionmentioning
confidence: 80%
“…It is generally accepted that plant defenses are attacker-specific (Howe and Jander 2008;Erb et al 2012), and even closely related, congeneric, plant species differ in their defenses against the same herbivore (van Dam and Raaijmakers 2006;Agrawal et al 2014). In addition, individual genotypes of the same species were shown to differ in the allocation of defensive compounds to AG or BG tissues when exposed to herbivory (Birch et al 1992(Birch et al , 1996Hol et al 2004).…”
Section: Integrating Different Response Levels Of Inducible Defensesmentioning
confidence: 99%
“…)-parasitoids Birch et al (1992) showed that different Brassica genotypes such as kale, rape and swede after inoculation with turnip root fly (D. floralis) eggs showed a similar response in glucosinolate metabolism. Total glucosinolate content in roots increased due to a two-to fourfold increase in indole-based compounds.…”
Section: Host Plants (Brassica Spp)-herbivoresmentioning
confidence: 99%